2009
DOI: 10.1074/jbc.m109.023754
|View full text |Cite
|
Sign up to set email alerts
|

Myosin II Tailpiece Determines Its Paracrystal Structure, Filament Assembly Properties, and Cellular Localization

Abstract: Non muscle myosin II (NMII) is a major motor protein present in all cell types. The three known vertebrate NMII isoforms share high sequence homology but play different cellular roles. The main difference in sequence resides in the C-terminal nonhelical tailpiece (tailpiece). In this study we demonstrate that the tailpiece is crucial for proper filament size, overcoming the intrinsic properties of the coiled-coil rod. Furthermore, we show that the tailpiece by itself determines the NMII filament structure in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
72
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 46 publications
(68 reference statements)
6
72
0
Order By: Relevance
“…7A). Thus in contrast to the complete tailpiece containing both the positively and negatively charged regions, the negatively charged The tailpiece has been shown to be important for determining the isoform specific morphology of NMII paracrystals (28). As the negatively charged region does not promote IICRod 1296 -1854 filament assembly it may be important in determining NMII paracrystal morphology.…”
Section: The Negatively Charged Region Of Nmii-c Tailpiece Regulates mentioning
confidence: 99%
See 3 more Smart Citations
“…7A). Thus in contrast to the complete tailpiece containing both the positively and negatively charged regions, the negatively charged The tailpiece has been shown to be important for determining the isoform specific morphology of NMII paracrystals (28). As the negatively charged region does not promote IICRod 1296 -1854 filament assembly it may be important in determining NMII paracrystal morphology.…”
Section: The Negatively Charged Region Of Nmii-c Tailpiece Regulates mentioning
confidence: 99%
“…NMII isoforms create different paracrystal morphology: NMII-A and NMII-B form large wide filaments (width measuring 1.21 Ϯ 0.4 nm and 1.22 Ϯ 0.38 nm, respectively) while NMII-C forms delicate thin filaments (0.32 Ϯ 0.07 nm) (28). Swapping the negatively charged region of either NMII-A or NMII-B with the negatively charged region of NMII-C resulted in thin filaments similar to NMII-C (0.269 nm Ϯ0.06 and 0.239 nm Ϯ0.04, respectively) ( Fig.…”
Section: The Negatively Charged Region Of Nmii-c Tailpiece Regulates mentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the reports on the role of the nonhelical tailpieces of vertebrate myosin IIs are based on in vitro studies of tail fragments of the mammalian nonmuscle myosin IIs NMIIA, NMIIB, and, to a lesser extent, NMIIC (22)(23)(24)(25)(26)(27). Phosphorylation by protein kinase C or casein kinase II of one or more serines in the nonhelical tailpieces of NMIIA and NMIIB was reported to inhibit assembly of NMIIB tail fragments but not of NMIIA tail fragments (23,24), as assayed by sedimentation, but in a later study was reported to inhibit the assembly of tail fragments of NMIIA (25).…”
Section: Discussionmentioning
confidence: 99%